Sintesis Biodiesel Menggunakan Katalis Heterogen CaO Batu Kapur dengan Support Fly Ash Pabrik Kelapa Sawit Teraktivasi Termal - Youfa, Rita; Pelita, Elda; Nirmala, Dyah; Desniorita, Desniorita; Jayanti, Regna Tri; Sahaq, Anang Baharuddin; Permadani, Resi Levi (Program Studi Teknik Kimia, Universitas Pamulang, 2026)
This study aims to produce biodiesel from Refined Bleached Deodorized Palm Oil (RBDPO) using a heterogeneous catalyst based on calcium oxide (CaO) derived from limestone andmodified with palm oil mill fly ash (FA) as a catalyst support. The limestone feedstock was first activated to obtain the CaO catalyst. Subsequently, the FA material was activated through calcination at 500°C. The CaO-FA catalyst was synthesized using the wet impregnation method and then calcined at 600°C. This catalyst was applied in the transesterification of RBDPO with methanol at various molar ratios. The study investigated the effect of different CaO-FA catalyst compositions (1:1, 2:1, and 3:1), and methanol:RBDPO molar ratios (8:1, 10:1, and 12:1) on biodiesel yield. The results demonstrated that both the CaO-FA catalyst ratios and the methanol:RBDPO molar ratios significantly influenced the biodiesel yield and the resulting Fatty Acid Methyl Ester (FAME) composition. Gas Chromatography-Mass Spectrometry (GC-MS) analysis revealed that the 3:1 CaO-FA composition with an 8:1 methanol:RBDPO molar ratio produced biodiesel with the highest methyl palmitate (C17H34O2) content of 88.99%, which meets the characteristics of high-quality biodiesel. These findings provide valuable insights into the development of CaO-FA-based heterogeneous catalysts for cost-effective and environmentally friendly biodiesel production, in line with government initiatives to promote renewable energy utilization.